2016
DOI: 10.1093/cvr/cvw211
|View full text |Cite
|
Sign up to set email alerts
|

High glucose facilitated endothelial heparanase transfer to the cardiomyocyte modifies its cell death signature

Abstract: Aims The secretion of enzymatically active heparanase (HepA) has been implicated as an essential metabolic adaptation in the heart following diabetes. However, the regulation and function of the enzymatically inactive heparanase (HepL) remain poorly understood. We hypothesized that in response to high glucose (HG) and secretion of HepL from the endothelial cell (EC), HepL uptake and function can protect the cardiomyocyte by modifying its cell death signature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…The LDL receptor-related protein 1, which is encoded by LRP1, is a large endocytic and signaling receptor [21]. An animal study showed that LRP1 expression was increased in cardiomyocytes isolated from acutely diabetic rats [22]. Other studies reported the upregulation of LRP1 in epicardial fat and skin from diabetic patients compared with control individuals, which was consistent with our findings [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…The LDL receptor-related protein 1, which is encoded by LRP1, is a large endocytic and signaling receptor [21]. An animal study showed that LRP1 expression was increased in cardiomyocytes isolated from acutely diabetic rats [22]. Other studies reported the upregulation of LRP1 in epicardial fat and skin from diabetic patients compared with control individuals, which was consistent with our findings [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…By acting directly on the apoptotic receptor and ligand, heparanase was able to provide protection of the cells against high glucose and H 2 O 2 induced cell-death. 46 The elucidation of transcription regulation by heparanase re-…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, heparanase is well established as a cancer drug target, and several inhibitors have progressed to clinical trials [31,34]. In recent years, heparanase has also been implicated in a range of other diseases, such as diabetes and its complications [35][36][37], kidney disease [38], atherosclerosis [39,40] and viral infections [41], to name a few, which continues to fuel research into this protein.…”
mentioning
confidence: 99%